Retrospective Comparative Analysis of Neonatal Mortality and Morbidity in Preterm Singleton and Multiple Births -Single Center Experience- - Mohammad Alhasoon MD; Bader Alqahtani MD; Mohamad Alreefi MD; Abdulaziz Homedi MD; Ghadah Alnami MD; Saif Alsaif MD; Kamal Ali MD (Res) (SAGE Publishing, 2024)
Objective. To compare mortality and major neonatal morbidities between singleton preterm infants and preterm infants of multiple gestations born <33 weeks' gestation. Method. Case-control study of preterm multiples and singletons <33 weeks' born at King Abdul-Aziz Medical City Riyadh (KAMC-R) between January 2017 and December 2020. Out-born infants and infants with lethal congenital abnormalities were excluded from the study. Mortality and major neonatal morbidities including bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), sepsis and surgical necrotizing enterocolitis (NEC) were compared between preterm singletons and multiples. Results. A total of 803 preterm infants were included: 567 (70.6%) were singletons, 158 (19.6%) were twins and 36 (4.5%) infants were higher multiples. Adjusted mortality before hospital discharge was significantly higher among preterm infants of multiple gestations compared to preterm singletons (12.3% vs 7.9%; P  = .003; AOR, 2.2; 95% CI, 1.3-3.7). Retinopathy of prematurity (ROP) needing treatment was significantly higher among preterm infants of multiple pregnancies compared to preterm singletons (11% vs 6.5%, P  = .033, AOR 1.1, 95% CI, 1.04-2.99). In addition, the incidence of bronchopulmonary dysplasia (BPD) at 36 weeks post menstrual age (PMA) (29.7% vs 20.5%; P = .003; AOR, 1.7; 95% CI, 1.2-2.5) and culture positive sepsis (24.2% vs 17.5%; P  = .044; AOR, 1.5; 95% CI, 1.01-2.2) were significantly higher among preterm infants of multiple pregnancy. There were no differences in mortality and adverse neonatal outcomes between twins and higher multiples. Conclusion. Preterm infants of multiple gestations suffered higher mortality and neonatal morbidities compared to preterm singleton infants despite a higher utilization of maternal antenatal steroids and better antenatal care.